2019
DOI: 10.1186/s42408-019-0053-9
|View full text |Cite
|
Sign up to set email alerts
|

Observed versus predicted fire behavior in an Alaskan black spruce forest ecosystem: an experimental fire case study

Abstract: Background: Fire managers tasked with assessing the hazard and risk of wildfire in Alaska, USA, tend to have more confidence in fire behavior prediction modeling systems developed in Canada than similar systems developed in the US. In 1992, Canadian fire behavior systems were adopted for modeling fire hazard and risk in Alaska and are used by fire suppression specialists and fire planners working within the state. However, as new US-based fire behavior modeling tools are developed, Alaskan fire managers are en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Studies of the self-limiting effects of wildfires also find 10 to 20 years to be an approximate cutoff beyond which previous fire perimeters fail to limit future wildfire spread (Collins et al 2009;Parks et al 2013Parks et al , 2015. Even so, we showed that 20-yearold thin-only treatments substantially reduced bole char height and crown consumption compared to controls, providing evidence that even older thinning treatments can help to reduce crown fire behavior or prevent excessive fire severity (Drury 2019). Treatment longevity is related to site productivity, and in many forests-including those found at this study site-it likely takes longer than 20 years for the seedlings and saplings remaining or establishing after treatment to become canopy fuels (Ritchie 2020).…”
Section: Discussionmentioning
confidence: 50%
“…Studies of the self-limiting effects of wildfires also find 10 to 20 years to be an approximate cutoff beyond which previous fire perimeters fail to limit future wildfire spread (Collins et al 2009;Parks et al 2013Parks et al , 2015. Even so, we showed that 20-yearold thin-only treatments substantially reduced bole char height and crown consumption compared to controls, providing evidence that even older thinning treatments can help to reduce crown fire behavior or prevent excessive fire severity (Drury 2019). Treatment longevity is related to site productivity, and in many forests-including those found at this study site-it likely takes longer than 20 years for the seedlings and saplings remaining or establishing after treatment to become canopy fuels (Ritchie 2020).…”
Section: Discussionmentioning
confidence: 50%
“…Studies of the self-limiting effects of wild res also nd ten to twenty years to be an approximate cutoff beyond which previous re perimeters fail to limit future wild re spread (Collins et al, 2009;Parks et al, 2013Parks et al, , 2015. Even so, we showed that 20-year-old thinonly treatments substantially reduced bole char height and crown torching compared to controls, providing evidence that even older thinning treatments can help to prevent or reduce crown re behavior (Drury, 2019). Treatment longevity is related to site productivity, and in many forests-including those found at this study site-it likely takes longer than 20 years for the seedlings and saplings remaining or establishing after treatment to become canopy fuels (Ritchie, 2020).…”
Section: Discussionmentioning
confidence: 56%
“…Fire is a fire behavior prediction simulator that calculates fire effect on stand characteristics [72]. Stacy A Drury [73] compared predicted fire behaviors from four models (BehavePlus, RedAPP, CanFIRE, and Crown Fire irritation and Spread System) with the observed fire behavior on the Alaskan black spruce forest. He studied the rate of fire movement, predicted flame length, energy, and ecological impact, and concluded that Canadian models, including RedAPP and CanFIRE provide more accurate predictions than BehavePlus.…”
Section: Scope Of ML Algorithms In Forest Fire Management Frame-workmentioning
confidence: 99%